A Review on Hypertension and Diabetes in India - Smita S. Swami; Sanjay C. Swami (New Frontiers in Medicine and Medical Research Vol. 17, 2021)
Type 2 diabetes mellitus (DM) and hypertension (HT) are two of the most common chronic noncommunicable diseases and multifactorial disorders that afflict both developed and developing countries, including India. Despite the fact that DM and HT are not among the top leading causes of death, such as cancer and stroke, the public’s attention is drawn to them because of their rising rates. Hypertension significantly raises the risk of coronary heart disease, stroke, nephropathy, and retinopathy in diabetes patients. When HT coexists with DM, the risk of CVD rises by 75%, contributing to the overall morbidity and mortality of an already high-risk population. India accounts for the majority of the diabetic and hypertensive population. This must be addressed by increased public awareness and appropriate government initiatives. The current review article discusses the comorbidity of HT and DM, as well as the current state of affairs in India. Both hypertension and diabetes should be diagnosed early and treated aggressively to prevent associated microvascular and macrovascular morbidity and mortality.